정유산업의 탄소중립 달성 방안: 전문가 심층면담을 중심으로 - 유재호(Yoo, Jae-Ho); 조연희(Jo, Yeon Hee); 김정인(Kim, Jeongin); 전의찬(Jeon, Eui-Chan) (한국기후변화학회지, 2022)
Carbon dioxide in the atmosphere reached its highest level in two million years as of 2019. Human-caused warming has increased at an unprecedented rate in the last 2000 years. As global warming worsens, various strategies are being developed to achieve carbon neutrality on a global scale. Highly energy-intensive industries like steel, petrochemicals, and oil refining, in particular, must take steps to achieve carbon neutrality. The goal of this research is to conduct in-depth interviews with 16 experts in the oil refining industry, an industry that emits large amounts of greenhouse gases, and to come up with a plan to achieve carbon neutrality in the oil refining industry. The results of this research suggest that policy support is required, such as the activation of overseas GHG mitigation project initiatives and tax breaks. Bio-energy and CCUS were highlighted as significant topics requiring technological development. Hydrogen-related businesses and eco-friendly gasoline filling station businesses are two new areas of interest to the oil refining industry. To boost citizen acceptance, it was determined that transparent carbon-neutral management and public relations are needed. This study performed in-depth interviews with 16 professionals in the oil refining business, asking questions from four primary categories and 12 subcategories. Governance implications such as policy assistance to attain carbon neutrality in the oil refining industry, technology development, discovery of new industries, and increased citizen acceptance were insights provided by the results of this study. KCI Citation Count: 0